OPTIMALISASI PADA PROMOSI DIGITAL DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN MENGGUNAKAN APLIKASI DIGITAL BUKU WARUNG PADA UMKM BISNIS BY MAMANAT - Cindy silviana; Dian Kusumawati; Titis Diah Pitaloka; May Lutfi Dwi Cahyani; Fina Muhibanah; Subhan Andzim Suharno; Vicky Subekti; Rizky Wahyudha Rosiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This community service aims to optimize digital promotion and financial report preparation for MSMEs through the utilization of the Buku Warung application in the By Mamanat business. Many MSMEs face challenges in adopting technology to enhance visibility and operational efficiency in the digital era. This program provides training to partners on utilizing social media as a promotional tool and using the Buku Warung application for more accurate financial record-keeping. The method used in this program begins with identifying the problems faced by the partners, followed by assistance in using financial applications and digital marketing strategies. The training results indicate an improvement in partners' managerial capabilities, as reflected in more organized financial reports and more effective business promotion. Thus, this community service is expected to contribute positively to the sustainability of MSMEs and serve as a reference for similar programs in the future.